Construction and Biological Evaluation of Small Libraries Based on the Intermediates within the Total Synthesis of Uvaretin. (15th April 2021) - Perera, Shashika; Fernando, Asantha; Dallman, Johnathan; Weeramange, Chamitha; Lansakara, Ashabha; Nguyen, Thi; Rafferty, Ryan J.
Abstract : Discovering therapeutic agents : New bioactive agents, either as sole or combinational agents, have been constructed through the synthetic manipulation of the intermediates within the total synthesis of the uvaretin class of natural products. It was found that increasing the hydrophobic character of the phenolic core correlates to a decrease in sole agent cytotoxicity. The synthesis of new, small chemical screening libraries (CSL) constructed from the intermediates of our total synthesis route of the uvaretin class of natural products is demonstrated herein. Numerous chalcone‐based CSLs with various substitution on the phenolic groups within the chalcone core were assembled. Through cytotoxicity investigations, it was found that the level of hydrophobicity of the phenolic core of the chalcones gives biases: less cytotoxicity with more hydrophobic cores. In addition, it was observed that the potentiation, evaluated with 6‐thiopurine in the pancreatic cancer cell line MIA PaCa‐2, is tunable by the inclusion of less‐hydrophobic character on the phenolic core. The role of the o ‐hydroxybenzyl group, present within the uvaretin family, was revealed to be cytotoxic in character. Merging all of the structure–activity relationship studies performed on the CSLs constructed in this effort led to the construction of a new chalcone hybrid possessing both a cytotoxic enone group and a small‐molecule‐potentiating, reduced enone group.